Production and characterization of a monoclonal antibody cross-reactive with most group A trichothecenes. - Fan, T S (1988)
A monoclonal antibody cross-reactive with most group A trichothecenes was produced by fusion of P3/NS-1/1-AG4-1 myeloma cells with spleen cells isolated from a BALB/c mouse that had been immunized with 3-acetyl-neosolaniol-hemisuccinate conjugated to bovine serum albumin. One stable clone, H159B1D5, which produced monoclonal antibody that bound with both T-2 toxin and diacetoxyscirpenol (DAS) was obtained after subcloning. Enzyme-linked immunosorbent assay (ELISA) revealed that the antibody belongs to the immunoglobulin G1 (kappa chain) isotype and had binding constants of 2.81 x 10(9), 1.05 x 10(9), and 1.57 x 10(8) liters per mole for T-2 tetraol tetraacetate, T-2 toxin, and DAS, respectively. The relative cross-reactivities of the antibody with T-2 tetraol tetraacetate, T-2 toxin, and DAS were 200, 100, and 20, respectively, with tritiated T-2 toxin as the marker ligand. The relative cross-reactivities for the above toxins were 667, 100, and 73, respectively, with tritiated DAS as the marker ligand. No cross-reaction with HT-2 and deoxynivalenol triacetate was observed in either system. By using this monoclonal antibody, an indirect ELISA for analysis of T-2 toxin was also developed. The linear portion of the standard curve for analysis of T-2 toxin in each analysis by radioimmunoassay and ELISA was in the range of 0.1 to 2 ng and 0.05 to 1.0 ng, respectively.